2007
DOI: 10.1002/jqs.1144
|View full text |Cite
|
Sign up to set email alerts
|

A case for a downwasting mountain glacier during Termination I, Verçenik valley, northeastern Turkey

Abstract: Field evidence of palaeoglacial records in the Verçenik valley in the Eastern Black Sea Mountains was examined and 19 samples for surface exposure dating with cosmogenic 10Be were collected with the aim of increasing knowledge on the amplitude and frequency of palaeoglacier advances in Anatolia. Glacial erosional features were mapped and the flow directions of the palaeoglaciers were determined. The Verçenik palaeoglacier advanced before 26.1 k ± 1.2 k yr. The Last Glacial Maximum (LGM) advance continued until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 51 publications
6
36
0
1
Order By: Relevance
“…The last decade has seen a large number of studies published in this region (Akçar et al 2007(Akçar et al , 2008(Akçar et al , 2014Sarıkaya et al 2008Sarıkaya et al , 2009Sarıkaya et al , 2014Zahno et al 2009Zahno et al , 2010Zreda et al 2011;Reber et al 2014;Ç iner et al 2015). These are either 10 Be or 36 Cl exposure age studies.…”
Section: Turkey and The Near Eastmentioning
confidence: 99%
“…The last decade has seen a large number of studies published in this region (Akçar et al 2007(Akçar et al , 2008(Akçar et al , 2014Sarıkaya et al 2008Sarıkaya et al , 2009Sarıkaya et al , 2014Zahno et al 2009Zahno et al , 2010Zreda et al 2011;Reber et al 2014;Ç iner et al 2015). These are either 10 Be or 36 Cl exposure age studies.…”
Section: Turkey and The Near Eastmentioning
confidence: 99%
“…Using cosmogenic radioisotope dating, Akçar et al (2007Akçar et al ( , 2008 found evidence that glacier expansion in the Kaçkar Mountains (NE Anatolia) started at ∼ 26 ± 1.2 ka BP and lasted until ∼ 18.3 ± 0.9 ka BP. Maximum glacier expansion occurred at ∼ 20.3 ± 1.5 ka BP in north-western Anatolia (Zahno et al, 2010), at ∼ 21.3 ± 0.9 ka BP in central Anatolia (Sarıkaya et al, 2009), and at ∼ 20.4 ± 1.3 ka BP in western Taurus (Arz et al, 2007); together with regional data from northern Anatolia: (c) δ 13 C from Sofular Cave (Fleitmann et al, 2009) reflecting changes in C3 and C4 plants and from Black Sea core 25-GC1: (d) arboreal pollen record (%) and Quercus curve (thin line); (e) xerophytic biome (%) with smoothed curve (thick line; simple moving 20 points average) (please note the reverse scale); (f) temperate biome (%) with smoothed curve (thick line); (g) concentration of marine dinocysts and acritarchs (specimens cm −3 ); (h) concentration of freshwater algae (specimens cm −3 ).…”
Section: Long-term Dynamicsmentioning
confidence: 99%
“…In northeast Anatolia, Akçar et al (2008) consider that glacial advance in the Kavron Valley very likely occurred during the Younger Dryas (12.8 ± 1.0 ka). In fact, there are traces of similar Younger Dryas glacial chronology in the mountains of southern Europe (Hughes et al, 2006).…”
Section: Sparse Glaciation In the Younger Dryasmentioning
confidence: 99%